NO regulates the strength of synaptic inputs onto hippocampal CA1 neurons via NO-GC1/cGMP signalling - Neitz, Angela (Pflügers Archiv, 2015)
GABAergic interneurons are the predominant source of inhibition in the brain that coordinate the level of excitation and synchronization in neuronal circuitries. However, the underlying cellular mechanisms are still not fully understood. Here we report nitric oxide (NO)/NO-GC1 signalling as an important regulatory mechanism of GABAergic and glutamatergic synaptic transmission in the hippocampal CA1 region. Deletion of the NO receptor NO-GC1 induced functional alterations, indicated by a strong reduction of spontaneous and evoked inhibitory postsynaptic currents (IPSCs), which could be compensated by application of the missing second messenger cGMP. Moreover, we found a general impairment in the strength of inhibitory and excitatory synaptic inputs onto CA1 pyramidal neurons deriving from NO-GC1KO mice. Finally, we disclosed one subpopulation of GABAergic interneurons, fast-spiking interneurons, that receive less excitatory synaptic input and consequently respond with less spike output after blockage of the NO/cGMP signalling pathway. On the basis of these and previous findings, we propose NO-GC1 as the major NO receptor which transduces the NO signal into cGMP at presynaptic terminals of different neuronal subtypes in the hippocampal CA1 region. Furthermore, we suggest NO-GC1-mediated cGMP signalling as a mechanism which regulates the strength of synaptic transmission, hence being important in gating information processing between hippocampal CA3 and CA1 region.
Published: 11 July 2014
Gesehen am 17.08.2020